Board of Editor - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2020)
Board of Editor PATRON :  Dean - Faculty of Civil, Environmental, Earth Sciences - ITS.                  Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE                    :   Head of Department  – Civil Engineering Department - ITSBOARD OF EDITOR               Chief Editor                          :               Ria Asih Aryani Soemitro ITS, Indonesia   h-index (GS = 10)Founding Editor                    :               Hitapriya Suprayitno ITS, Indonesia  h-index (GS = 9)         Managing Editor                   :               Trihanyndio Rendy Satrya  ITS, Indonesia  h-index (GS = 2)                                                           Mahendra Andiek Maulana  ITS, Indonesia  h-index (GS = 2)Editor                                  :               Data Iranata  ITS, Indonesia  h-index (GS =3)                                                           Alex Abdi Chalik PUPR, Indonesia  h-index (GS =  -)                                                            Danang Parikesit UGM, Indonesia  h-index (GS =  8)                                                           Achmad Wicaksono UB, Indonesia  h-index (GS=  9)                                                           Maimunah Sapri UTM, Malaysia  h-index (GS = 16)                                                           Wahyu Caesarendra UBS, Brunei Dar es Salam   h-index (GS = 19) Address                             :                 Editor JIFAM – Room  J - 201                                                           Departement of Civil Engineering                                                                      Institut Teknologi Sepuluh Nopember                                                           ITS Campus, Sukolilo, Surabaya 60111                                                           Email : jurnal.jifam@gmail.com                                                             Website: https://iptek.its.ac.id/index.php/jifam           Reviewer for this EditionRia Asih Aryani Soemitro, Insitut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Hitapriya Suprayitno, Insitut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Mahendra Andik Maulana, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Trihanyndio Rendy Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, IndonesiaJanuarti Jaya Eka Putri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Akhmad Wicaksono, Universitas Brawijaya (UB), Malang, Indonesia.